AN OPTIMAL ORDER QUANTITY OF SPARE PARTS TO MINIMIZE TOTAL INVENTORY COST USING PERIODIC REVIEW APPROACH (R,s,S) METHOD IN PT XYZ BANDUNG - Feviana Betsi Purba; Luciana Andrawina; Murni Dwi Astuti (School of Industrial and System Engineering, Telkom University, 2018)
The availability of spare parts is very crucial thing for manufacturing company in order to support the continuity of production activities. PT XYZ is a manufacturing company which produces thread into fabric. In this case, inventory control of spare part is not properly managed. Inventory position of spare parts in warehouse is always more than inventory policy of the company itself or called overstock which causes total inventory cost is always high. Company only consider on the order fulfillment of spare parts to prevent downtime on the machine that increase performance of production. Hence, order quantity of spare parts is always excessive or not optimal. In this research, global inventory policy conducted in order to minimize total inventory cost is periodic review approach (R, s, S) method. This inventory policy will be calculated using power approximation and obtained total saving cost of holding cost by 31 % while total saving cost of order cost decreased by 7 %. Overall, total inventory cost minimized by 7 % or equal to Rp138.902.742. Keywords—Inventory, Overstock, Spare Parts, Periodic Review, Power Approximation